2015
DOI: 10.1002/bio.2904
|View full text |Cite
|
Sign up to set email alerts
|

Binding properties of palmatine to DNA: spectroscopic and molecular modeling investigations

Abstract: Palmatine, an isoquinoline alkaloid, is an important medicinal herbal extract with diverse pharmacological and biological properties. In this work, spectroscopic and molecular modeling approaches were employed to reveal the interaction between palmatine and DNA isolated from herring sperm. The absorption spectra and iodide quenching results indicated that groove binding was the main binding mode of palmatine to DNA. Fluorescence studies indicated that the binding constant (K) of palmatine and DNA was ~ 10(4)L·… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Proteomic analysis based on mass spectrometry and bioinformatics is a powerful and high-throughput technique to identify global differentially expressed proteins (DEPs) (Yang et al 2018). The desire to fully understanding the pharmacological effects of palmatine and its derivatives and elucidate their mechanisms using genomics, proteomics and other advanced approaches has attracted scientists (Mi et al 2015). However, differences in the global expression of proteins in mucosal epithelial cells treated with palmatine compared to control cells have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Proteomic analysis based on mass spectrometry and bioinformatics is a powerful and high-throughput technique to identify global differentially expressed proteins (DEPs) (Yang et al 2018). The desire to fully understanding the pharmacological effects of palmatine and its derivatives and elucidate their mechanisms using genomics, proteomics and other advanced approaches has attracted scientists (Mi et al 2015). However, differences in the global expression of proteins in mucosal epithelial cells treated with palmatine compared to control cells have not been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other isoquinoline alkaloids, palmatine can bind to DNA through groove-binding mechanism by forming hydrogen and van der Waals bonds. 79 Other studies demonstrated that palmatine binds to poly (A) and tRNA, 80,81 adeninethymine homo and hetero polymers through the intercalation. 82 It also binds preferentially to DNAs that have a long sequence of AT base pairs.…”
Section: Safety Evaluations Of Palmatinementioning
confidence: 99%
“…It has been proven by different techniques that this compound intercalates into the ctDNA bases and also that the compound has the ability to bind to the DNA minor groove through hydrogen bonds and Van der Waals interactions. Groove binding predominates over electrostatic interactions and intercalation (Li, Shuang, & Dong, ; Mi et al, ). PLT has a strong affinity for DNAs that have a long sequence of AT base pairs.…”
Section: Pharmacology Of Pltmentioning
confidence: 99%